2009
DOI: 10.1021/ja9066139
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Conjugated Polymers with Donor−π-Bridge−Acceptor Side Chains for High Performance Solar Cells

Abstract: Two new conjugated polymers have been designed and synthesized for polymer solar cells. Both of them exhibit excellent photovoltaic properties with a power conversion efficiency as high as 4.74%. Different from the traditional linear donor-acceptor (D-A) type conjugated polymers, these newly designed polymers have a two-dimensional conjugated structure with their tunable acceptors located at the end of D-A side chains and connected with the donors on the main chain through an efficient pi-bridge. This approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
278
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(292 citation statements)
references
References 23 publications
13
278
1
Order By: Relevance
“…The field activation parameters ␥ are quite different though: For the thicknesses studied the ␥'s are negative. These results indicate that the experimentally observed negative ␥ values 47 can be a result of blend morphology. However, we stress that this is by no means general: The complex balance between field and density dependences of the mobility ultimately determines ␥ and this will depend on the exact blend morphology as well as on other material parameters.…”
Section: Comparison With Experimental Datasupporting
confidence: 57%
See 2 more Smart Citations
“…The field activation parameters ␥ are quite different though: For the thicknesses studied the ␥'s are negative. These results indicate that the experimentally observed negative ␥ values 47 can be a result of blend morphology. However, we stress that this is by no means general: The complex balance between field and density dependences of the mobility ultimately determines ␥ and this will depend on the exact blend morphology as well as on other material parameters.…”
Section: Comparison With Experimental Datasupporting
confidence: 57%
“…͑9͒ was used to fit SCL currents in conjugated polymers and blends thereof. 47,48 This procedure makes possible the quantification of the apparent bias dependence of the mobility, but it ignores the density dependence of mobility and is, therefore, not strictly correct. In fact, Tanase et al showed that the enhancement of the SCL hole current in diodes made of PPV derivatives originates from the density dependence of the mobility rather than from its field dependence, at least at room temperature.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a dramatic improvement was obtained in PBDT-TPD based PSCs through a simple tuning of the side chain length, and a high PCE up to 8.5% was achieved by Cabanetos and coworkers [31]. However, compared with aforementioned cases, only a very few of studies took considerations of the substitution position effect of alky chains in studies of photovoltaic polymers [35][36][37]. Therefore, to investigate the effect of substitution positions of the alkyl chains should be of great importance for structure optimization of photovoltaic polymers, and this will provide guidance for designing high performance photovoltaic materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, greater efforts have been devoted to seek new possibilities for use in optoelectronic devices such as Polymer Light Emitting Diodes (PLEDs) [5][6][7][8][9][10][11], Polymer Photovoltaic Cells (PPCs) [12][13][14][15][16][17][18][19][20][21][22][23] and Polymer Field Effect Transistors (PFET) [24][25][26][27][28][29][30][31][32][33]. The field of PLEDs is still an active research area since the first conjugated conducting or semiconducting polymeric material, poly(p-phenylene-vinylene) (PPV), was reported by Burroughes et al in 1990 [34].…”
Section: Introductionmentioning
confidence: 99%